Música na educação infantil: estratégias, propostas e concepções de ensino de música em escolas de ensino regular do município de Vitória (ES) - Cintia Dutra Tavares (2013)
In August 2008, the Brazilian Senate approved the Law 11,769, which introduced music in every Brazilian Kindergarten, Elementary, Grade and High Schools. The city of Vitoria (ES) has been looking for alternatives to include music within the school context, even before this Law. In 2007, the prerequisites for teachers in the field of Visual Arts and Art Education were proposed, as already pointed out by the Lei de Diretrizes e Bases (1996). After a public exam, music teachers with higher education were hired to work in the Centros Municipais de Educação Infantil (CMEIs), in the city of Vitoria. However, during this period, several difficulties concerning music education in these public schools have arisen. Given this context, it became necessary to investigate more deeply this subject, in order to identify and understand what is going on concerning music teaching processes at the CMEIs in Vitória (ES). Data were obtained through interview and questionnaire. The speeches of the teachers in their interviews and in the open questions of the questionnaires were analyzed through the Content Analysis technique. The results showed a dissatisfaction of the music teachers concerning, specially, their university education. Although many of these results were similar to those found in other researches which were conducted in other parts of the country, we found that some of the demands and ideas of these professional music teachers were more refined if compared to what was exposed by the classroom teachers who participated in the other studies. This suggests that, even with many problems to face, there have been advances in relation to early childhood music education in the city of Vitoria.